Immunostimulatory activity of water-extractable polysaccharides from Cistanche deserticola as a plant adjuvant in vitro and in vivo - Ailian Zhang; Xiumei Yang; Quanxiao Li; Yang Yu; Gan Zhao; Bin Wang; Daocheng Wu (2018)
A safe and effective vaccine adjuvant is important in modern vaccines. Various Chinese herbal polysaccharides can activate the immune system. Cistanche deserticola (CD) is a traditional Chinese herb and an adjuvant candidate. Here, we confirmed that water-extractable polysaccharides of CD (WPCD) could modulate immune responses in vitro and in vivo. In a dose-dependent manner, WPCD significantly promoted the maturation and function of murine marrow-derived dendritic cells (BM-DCs) through up-regulating the expression levels of MHC-II, CD86, CD80, and CD40, allogenic T cell proliferation, and the yields of IL-12 and TNF-α via toll-like receptor4 (TLR4), as indicated by in vitro experiments. In addition, its immunomodulatory activity was also observed in mice. WPCD effectively improved the titers of IgG, IgG1 and IgG2a and markedly enhanced the proliferation of T and B cells, the production of IFN-γ and IL-4 in CD4+ T cells and the expression level of IFN-γ in CD8+ T cells better than Alum. Furthermore, WPCD could markedly up-regulate the expression levels of CD40 and CD80 on DCs in spleen and down-regulate the Treg frequency. The study suggests that polysaccharides of Cistanche deserticola are a safe and effective vaccine adjuvant for eliciting both humoral immunity and cellular immunity by activating DCs via TLR4 signaling pathway.